Management of unexpected placenta accreta spectrum cases in resource-poor settingsAJOG Global Reports at a Glance - Rozi Aditya Aryananda, MD; Albaro José Nieto-Calvache, MD; Johannes J. Duvekot, PhD; Aditiawarman Aditiawarman, PhD; Marcus J. Rijken, PhD (Elsevier, 2023)
BACKGROUND: On a global scale, cases of placenta accreta spectrum are often just identified during cesarean delivery because they are missed during antenatal care screening. Routine operating teams not trained in the management of placenta accreta spectrum are faced with difficult surgical situations and have to make decisions that may define the clinical outcomes. Although there are general recommendations for the intraoperative management of placenta accreta spectrum, no studies have described the clinical reality of unexpected placenta accreta spectrum cases in resource-poor settings. OBJECTIVE: This study aimed to describe the maternal outcomes of previously undiagnosed placenta accreta spectrum managed in resource-poor settings in Colombia and Indonesia. STUDY DESIGN: This was a retrospective case series of women with histologically confirmed placenta accreta spectrum treated in 2 placenta accreta spectrum centers after referral from remote resource-poor hospitals. Clinical outcomes were analyzed according to the initial type of management: (1) no cesarean delivery; (2) placenta left in situ after cesarean delivery; (3) partial removal of the placenta after cesarean delivery; and (4) post-cesarean hysterectomy. In addition, we evaluated the use of telemedicine by comparing the outcomes of women in hospitals that used the support of the placenta accreta spectrum center during the initial surgery. RESULTS: A total of 29 women who were initially managed in Colombia (n=2) and Indonesia (n=27) were included. The lowest volume of blood loss and the lowest frequency of complications were in women who underwent deferred cesarean delivery (n=5; 17.2%) and in those who had a delayed placental delivery (n=5; 20.7%). Five maternal deaths (14%) occurred in the group that did not receive telehelp, and 4 women died of irreversible shock because of uncontrolled bleeding. CONCLUSION: Previously undiagnosed placenta accreta spectrum in resource-poor hospitals was associated with a high risk of maternal mortality. Open-close abdominal surgery or leaving the placenta in situ seem to be the best choices for unexpected placenta accreta spectrum management in resource-poor settings. Telemedicine with a placenta accreta spectrum center may improve prognosis.